Stability and Change in Intelligence From Age 12 to Age 52: Results From the Luxembourg MAGRIP Study. - Schalke, Daniela; Brunner, Martin; Geiser, Christian; Preckel, Franzis; Keller, Ulrich; Spengler, Marion; Martin, Romain (Developmental Psychology, 2013)
The present longitudinal study tackled 2 key aspects of the development of intelligence across a 40-year time period from age 12 to age 52 concerning (a) stability and change in the structure of intelligence with reference to the age differentiation-dedifferentiation hypothesis (how different cognitive abilities relate to each other across age) and (b) differential stabilities (the rank ordering of persons' intelligence levels across time). To this end, we drew on 2 structural conceptions of intelligence: (a) the extended Gf-Gc model to study broad cognitive abilities and (b) the 3-stratum model to decompose cognitive change into processes that are shared by all broad abilities (attributable to general cognitive ability g) and processes specific to a certain ability (independent of g). Data were obtained for 344 persons (56.4% female). The results showed that people differ more greatly over time with respect to ail broad abilities except for fluid reasoning, whereas the rank ordering of persons on all broad abilities remains remarkably stable. These combined results yielded substantial gap-widening effects from age 12 to age 52 years that were mainly accounted for by a substantial increase in g variance in combination with a high differential stability of g. Moreover, the increase in g variance reflects an increase in covariance among different broad abilities, which indicates that the different constructs relate more closely to each other at age 52 compared to age 12 (i.e., age dedifferentiation). Two theoretical explanations of this change in the structure of intelligence are discussed (common cause hypothesis and investment theory).